Kinesiology analysis of athletics at the ancient Olympics and of performance differences between male and female Olympic champions at the modern games in running, swimming and rowing - Stefani, R. (Athens Journal of Sport, 2017)
Kinesiology and physics were employed to better understand the performance of male and female athletes in the Ancient and in the Modern Olympic Games. In what we now call the Ancient Olympics (actually the Pan-Hellenic Games at Olympia), then open only to men, athletes competing in the long jump (part of the pentathlon) carried 1.5-3 kg weights called halteres. By training today`s athletes, we have learned that by coordinating the backward and forward thrusting of those weights, about 5% in distance can be gained. In the javelin (also part of the pentathlon) a cord wound around the javelin unwrapped as the javelin was thrown, providing spin stabilization. Performance enhancing drugs were legal at the Ancient Olympics. When women competed in the Heraea Games at Olympia, they ran 5/6 (83%) as far as men, which was the female/male performance ratio of 1928 Olympic champions when women resumed athletics competition. Regarding the Modern Olympics, for running, swimming and rowing, using physics and kinesiology, equations for the velocity ratios of female/male elite athletes were derived and then populated with parameters from studies of over 2000 athletes. Assuming equal training and efficiency, the female/male ratio for running velocity simplifies to the relative female/male lean-toweight ratio; while for swimming and rowing, the velocity ratio becomes the 8/9th power of the relative lean-to-weight ratio, a remarkable similarity. For the average of Olympic champions in two time frames from 1980 until the present, the actual velocity ratios of about 90% are within tenths of a percent of the expected values, except for running where women have a 1% inefficiency due to longer-than men stride length (relative to height) induced by hip-height geometry. That extra 1% of wear strongly suggests that female athletes should strengthen knee joints to reduce the tendency of females to have six times the likelihood of ACL ligament tears as men.